Haikyu!!. 27, An opportunity accepted - Furudate, Haruichi, 1983- (Shonen Jump manga., 2018)
"Round one of the Spring Tournament begins! Karasuno faces off against the Tsubakihara Academy, a team that's come to nationals for the second year in a row. Mistakes and problems pile up as the huge gymnasium begins to mess with Karasuno's ability to navigate the new court. Kageyama begins to acclimate to the new environment, but the Tsubakihara players aren't pushovers...and they have a secret weapon!"--Back cover.